Errors Analysis of The Sentences Made by Freshmen of English Department - Savitri, Wiwiet Eva; Akhiriyah, Suvi (IJET (Indonesian Journal of English Teaching), 2016)
Writing sentence is not a simple task. Yet, it is found many times that even students of latest semesters are unable to compose good writing text due to their inability in producing good sentences. It is an unfortunate because ability in writing good sentences is the fundamental for the next level of writing. The failure of senior students to make good sentences triggers questions on what materials to focus on and how to conduct teaching and learning in the writing and grammar classes. In line with those, this study tries to reveal the errors freshmen students usually make in writing sentences. It is expected that the result of this study helps lecturers to choose appropriate materials and teaching techniques. The results of this study show that most errors are found in terms of grammar, mechanic, logic, and spelling. Hence, it is suggested that freshmen practice sentence writing more to practice the grammar rules, spelling, and mechanic as well as to sharpen their ability in building logical sentences.